1991
DOI: 10.1177/019459989110500314
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Enuresis in Children with Upper Airway Obstruction

Abstract: This study presents the results of our experience with 115 children between the ages of 3 and 19 years who have had symptoms of upper airway obstruction and nocturnal enuresis. Twelve children had secondary enuresis, and 103 children had primary enuresis. Surgical removal of upper airway obstruction led to a significant decrease in or complete cure of nocturnal enuresis in 87 (76%) of the children studied. Eleven children were also studied with polysomnographic tracings in an attempt to determine a relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(42 citation statements)
references
References 8 publications
1
37
0
4
Order By: Relevance
“…Weider et al found that the diurnal ADH rhythm disappeared in these patients [11]. In fact, dysrhythmic ADH secretion is a result of an atrial natriuretic response to upper airway resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Weider et al found that the diurnal ADH rhythm disappeared in these patients [11]. In fact, dysrhythmic ADH secretion is a result of an atrial natriuretic response to upper airway resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Nocturnal enuresis Children with simultaneous symptoms of upper airway obstruction benefit from TE [151], [554] (grade B), [555] (grade C).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining enuretic children seen at our outpatient ward had major behavioral or psychological problems, heart or endocrine diseases or allergic diatheses such as asthma [11]. These 80 children (11.39%) had changing success rates with any therapeutic measure: the better they were with respect to their disease, the better the temporary success of therapeutic interaction.…”
Section: Methods and Resultsmentioning
confidence: 99%